O léxico no século XVI: um estudo do idioma brasileiro - Mórra, Eunice Martins (2006)
This paper, based on the research line of History and Description of Portuguese, implies an exploratory investigation, whichg object of study is circumscribed to the Brazilian Portuguese vocabulary of the XVI century. It is claimed that idiomaticity is inscribed in the transformation of the archaic-Provençal Portuguese that, transported to the Brazilian lands with the colonists who moved bringing it, was cultivated as it was in the soil of the new colony. In this process of cultivation, resulting the cultural adaptation of the white, the native and the negro people, that vocabulary would have been renovated to be accustomed to the context of another territory; in such a manner it would incorporate new semias and, thus, supply the lack of an authentic Portuguese archaic-Provençal vocabulary. However, those new semias are still unsatisfactory, and it would be necessary to incorporate to its lexical field words of native and African origins, because of the new geography, fauna and flora. From this sememic changing process and incorporations new/other lexicalizations will appear, contrasting with the Brazilian Portuguese itself, through the edification of new architectures, which sup port is the same linguistic system: the one that qualifies the processes of codification of the world knowledge, formalized by the Portuguese language. The distinction between structure and architecture granted the differentiation between language from idiom a starting point adopted to examine the idiomatization of the archaic-Provençal Portuguese, being its parameter the processes of lexicalization and to consider both Brazilian Portuguese and Portugal s, as well as the one of the other nations as idioms produced by differentiated cultural languages which lived together - and still live in different geographical spaces and that, nowadays, typify distinct territories that became National States. Those different languages which had made those territories bilingual let themselves to be inscribed in the vocabulary system of those idioms, in order to grant them with visions of world that, although distinct, present similarities in terms of form which frame the field of their respective vocabularies. Guided by a general objective to try to explain the permanencies by dislocation models concerned to the structure and organization of this idiomatization process the investigative way is traced by two focuses. One that configures historiographical characteristic of the constitution of the idiom in the land of the parrots ; other that concerns to the images of the linguistic studies that favour the lexicon as instancy capable of pointing out similarity through the differences among models of organization and representation of world knowledge formalized by a unique linguistic system. From the results obtained, by means of analytical procedures oriented by the study of the discursive -semantic fields, the result is an archaic Provençal Portuguese which was implanted in Brazil which becomes an idiom and the official language of a transmuted colony in National State at the XIX century. Such idiomatization presents differences not significant in the grammatical area and not allowing to considerate the existence of different languages. In the lexical area, this process of idiomatization , which implies the construction of differentiated points of view through which knowledge of world are organized, framed and formalized by language categories, may qualify Brazilian idiom differently from that of Portugal